Visualisasi Seni Sebagai Aspek Kreatif Periklanan - Permana, Gandara (Institut Bisnis dan Teknologi Indonesia, 2018)
Advertising is an in-depth creative process with a variety of supporting factors. One of the constituent elements is the creative strategy aspect. Advertising creative strategy is a tool to generate fresh and creative ideas that represent advertised products. The context of art as part of society's lifestyle becomes one of the commodities to be exploited. This study used descriptive qualitative method. This topic is analyzed by visual content approach through dissecting advertising visualization with the context of its art medium, message and linking visualization of art as creative aspect of advertisement so as to produce persuasion element for consumer audiences. The results obtained are the use of art medium in advertising as an approach to the audience by utilizing the momentum, situations and emotions that can persuade audiences. Visualization of the ad is a moment of celebration with the nuance of kinship or the expression of the life style of the young people who care about the traditional values ​​of the nation.